Mitochondrial DNA Variation Correlated With the High Altitude Intolerance in Chinese Young Han Males - Li, Zongbin; Liu, Chunwei; Guo, Jun; Shi, Yajun; Li, Yang; Wang, Jinli; Zhou, Shanshan; Chen, Yundai (Frontiers in Cardiovascular Medicine, 2022)
Objective: Acute exposure to hypobaric hypoxia can trigger acute mountain sickness (AMS), while the exact mechanism has not been fully revealed. Whether genetic factors play the role in the susceptibility of various high-altitude diseases has also gained much interest. The correlation between point mutations of mitochondrial DNA (mtDNA) and AMS was further explored in the present study. Methods: A total of 84 young Han males residing at low altitude were taken to an elevation of 4000 m within 40 hours. We collected data of heart rate, blood pressure, peripheral oxygen saturation (SaO2) and obtained blood samples, at sea level and at altitude. AMS was diagnosed using the revised version of Lake Louise Questionnaire Score. Sequencing was utilized to identify the association between mtDNA alleles and the occurrence of AMS. We also assessed the association between the presence of AMS and physiological variables, provided a preliminary discussion of association between genotypic and phenotypic variation. Results: The percentage of neutrophils (OR 1.06, 95% CI 1.01-1.12, P=0.034) and SaO2 level (OR 0.87,95% CI 0.79-0.95, P=0.004) were independently associated with the development of AMS. A4576G was a risk factor for AMS (OR 6.27, 95% CI 1.2-32.7). T11613C (OR 0.10, 95% CI 0.01-0.83), A8923G (OR 0.15, 95% CI 0.03-0.76) and T5543C (OR 0.19, 95% CI 0.04-0.95) were protective factors for AMS. The level of SaO2 was significantly lower in the individual with A4576G mutation as compared with the individual without A4576G mutation (68.1±7.9 vs 75.8±6.1, P=0.001). The level of serum sodium was significantly higher in the individual with A8923G mutation as compared the individual without A8923G mutation (144.6±1.9 vs 143.2±1.9, P=0.027) . Conclusions: The increase of neutrophils and the disability to preserve oxygen saturation may be associated with the high altitude intolerance in young Chinese young Han males. A4576G is the risk factor for AMS. T11613C, A8923G and T5543C are protective factors for AMS. The role of A8923G mutation may correlate with the sodium and water balance and the role of the A4576G mutation may be related to the disability to maintain blood oxygen level after quickly entering the plateau.